A nanofibrous molybdenum sulfide / carbon thermal battery composite positive electrode material, a preparation method and application thereof
Patent Information
- Application Number
- CN202610906404.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-23
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2046-06-23
AI Technical Summary
该方法容易造成前驱体团聚、溶剂残留,在热电池激活瞬间的高温热冲击以及随后的放电过程中,可能造成相分离、局部烧结或结构坍塌,难以兼顾高活性物质利用率、快速传质传荷和长期放电稳定性
(1)本发明以钼盐作为钼源、高分子化合物作为碳源,采用高压静电纺丝和高温硫化焙烧相结合的方式制备纳米纤维状 MoS2/C 热电池复合正极材料,使 MoS2在碳纤维形成过程中原位生成并包含于纳米碳纤维中,有利于改善传统机械混合方式中活性材料分布不均、界面接触不充分和导电网络不连续的问题。
Smart Images

Figure CN122426780B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery materials technology, specifically to a nanofiber-like molybdenum sulfide / carbon thermal battery composite cathode material, its preparation method, and its application. Background Technology
[0002] A thermal battery is a type of storage battery that uses an inorganic salt as its electrolyte. This type of electrolyte is solid at room temperature, and no ion exchange reaction occurs at the positive and negative electrodes. During operation, an internal heating source is activated, causing a rapid temperature rise. The solid molten salt melts and becomes an ionic conductor, allowing the battery to output energy. Compared to aqueous chemical storage batteries, thermal batteries have higher conductivity due to their molten salt ionic conductor electrolyte, enabling discharge at high current densities and achieving high-energy, high-power output. They require no electrolyte filling process, no secondary installation or regular maintenance, and activation time is less than 1 second. They also have a wide operating temperature range, functioning from -60 to 500°C, demonstrating strong environmental adaptability. Therefore, they are widely used in power systems requiring long-term storage, rapid activation, and instantaneous high-power output. A thermal battery typically consists of individual cells, a heating system, an insulation system, an activation system, terminals, a casing, and a cover. The individual cell is the core unit for electrochemical energy conversion and usually includes a positive electrode material, an electrolyte, and a negative electrode material. For thermal batteries, the cathode material not only directly participates in the electrochemical reaction, but also needs to maintain sufficient thermal stability, structural stability, and conductivity under battery activation and high-temperature discharge conditions. Therefore, the intrinsic thermal stability, electronic conductivity, ion diffusion characteristics, interfacial contact state with the molten salt electrolyte, and structural changes during discharge of the cathode material all have a significant impact on the activation rate, discharge voltage plateau, discharge capacity, power output capability, and safety of the thermal battery.
[0003] Currently, the commonly used cathode materials for thermal batteries are transition metal sulfides such as FeS2 and CoS2. While these materials possess certain electrochemical activity and a basis for engineering applications, they still have significant shortcomings in high-power, high-current-density output scenarios. On one hand, FeS2 and CoS2 have relatively low electronic conductivity, resulting in significant electron transport resistance within the electrode. When the thermal battery undergoes high-current discharge, severe ohmic and concentration polarization easily occurs, leading to a decrease in discharge voltage, insufficient capacity release, and potentially prolonging the time it takes for the thermal battery to reach a stable operating state. On the other hand, FeS2 and CoS2 have limited thermal stability. Under the high-temperature environment inside the thermal battery and the additional heat generated by high-power discharge, the cathode active material is prone to decomposition, producing sulfur vapor or other byproducts. After diffusing inside the battery, the sulfur vapor may react with the lithium alloy anode, further releasing heat and exacerbating heat accumulation inside the battery, potentially inducing thermal runaway in severe cases. To improve the conductivity and thermal stability of traditional cathode materials, modifications are typically made by adding conductive agents, reducing the particle size of the active material, controlling the material morphology, or constructing composite cathodes. Combining metal sulfides with carbon materials, such as combining MoS2 with carbon materials to prepare nanofibers, can improve the overall conductive network of the electrode and reduce the internal resistance of the battery to a certain extent. Nanostructuring active materials can shorten the ion diffusion path and improve reaction kinetics. Patent application CN 110289389A discloses a molybdenum disulfide / carbon nanofiber composite material, its preparation method, and its application. This method prepares molybdenum disulfide / carbon nanofibers by electrospinning and carbonization using molybdate, sulfides, and water-soluble polymers. However, this method is prone to precursor agglomeration and solvent residue. During the high-temperature thermal shock at the moment of activation of the hot battery and during subsequent discharge, it may cause phase separation, local sintering, or structural collapse, making it difficult to simultaneously achieve high utilization of active materials, rapid mass and charge transfer, and long-term discharge stability. Therefore, it is necessary to develop a MoS2 / C composite cathode material and its preparation method suitable for the working environment of thermal batteries, so that MoS2 can be uniformly contained in carbon nanofibers, and the thermal stability, conductivity, interfacial reaction efficiency and structural stability of the material can be improved through the nanofiber network, thereby improving the discharge capacity, discharge stability and safety of thermal batteries under high current and high power output conditions. Summary of the Invention
[0004] To address the aforementioned limitations of existing technologies, the present invention aims to provide a nanofiber-like molybdenum sulfide / carbon thermal battery composite cathode material, its preparation method, and its applications. The present invention first prepares a molybdenum salt into a spinning solution and performs electrospinning, resulting in a uniform distribution of the molybdenum salt within the nanofibers. Then, heat treatment is used to sulfide the molybdenum salt while simultaneously carbonizing the nanofibers. The MoS2 / C composite cathode material prepared by this method exhibits high thermal stability, resisting the instantaneous thermal shock during battery activation, making it suitable for the discharge environment of thermal batteries. It reduces the decomposition rate of the cathode material, increases output capacity, lowers interfacial impedance and internal battery impedance, strengthens the contact between the cathode and electrolyte interface, facilitating rapid transfer of ions and electrons within the material, and reduces the volume expansion effect during battery discharge, ensuring battery discharge stability and safety.
[0005] To achieve the above objectives, the present invention adopts the following technical solution: In a first aspect, the present invention provides a method for preparing a nanofiber-like molybdenum sulfide / carbon thermal battery composite cathode material, comprising the following steps: (1) Add the carbonizable polymer to the spinning solvent and mix evenly, then add molybdenum salt and stir evenly to obtain the spinning solution. Obtain nanofiber film by high voltage electrospinning and vacuum drying. (2) The nanofiber film was mixed with sulfur powder and heat-treated under a protective atmosphere to obtain nanofiber molybdenum sulfide / carbon thermal battery composite cathode material.
[0006] Preferably, in step (1), the carbonizable polymer is selected from at least one of polyvinylpyrrolidone, polyester, polyamide, polyvinyl alcohol, polyvinylidene fluoride, polyacrylonitrile, or polystyrene; the spinning solvent is selected from at least one of methanol, ethanol, N,N-dimethylformamide, dichloromethane, chloroform, tetrahydrofuran, N-methylpyrrolidone, dimethylacetamide, or dimethyl sulfoxide; and the molybdenum salt is selected from at least one of molybdenum sulfate, molybdenum chloride, molybdenum nitrate, or molybdenum acetate.
[0007] Preferably, in step (1), the temperature at which the mixture is homogenized is 30~60℃.
[0008] Preferably, in step (1), the mass ratio of the carbonizable polymer to the spinning solvent is 5:95-15:85; and the mass ratio of the carbonizable polymer to the molybdenum salt is 10:90-40:60.
[0009] Preferably, in step (1), the parameters of the high-voltage electrospinning are: spinning current of 0.5-2mA, spinning voltage of 20-50kV, distance between spinning needle and collector of 15-40cm, spinning speed of 0.05-0.30rpm, spinning temperature of 20-50℃, and spinning humidity of 30-50%.
[0010] Preferably, in step (1), the vacuum drying temperature is 120-220℃ and the time is 8-24h.
[0011] Preferably, in step (2), the mass ratio of the nanofiber film to sulfur powder is 30:70-50:50.
[0012] Preferably, in step (2), the heating rate of the heat treatment is 3-12℃ / min, the temperature is 500-800℃, and the time is 3-7h; the flow rate of the protective atmosphere is 20-60sccm.
[0013] If the heat treatment temperature is too low, it will be difficult to fully carbonize and complete the sulfidation reaction; if the heat treatment time is too short, the molybdenum source and the sulfur source will not be able to fully react.
[0014] In a second aspect, the present invention provides a nanofiber-like molybdenum sulfide / carbon thermal battery composite cathode material obtained by the above preparation method, comprising carbon fibers and two-dimensional layered MoS2 contained therein; the two-dimensional layered MoS2 is multilayered MoS2 nanosheets; the multilayered MoS2 nanosheets are generated in situ and embedded within the carbon fibers; the specific surface area of the nanofiber-like molybdenum sulfide / carbon thermal battery composite cathode material is 286–400 m². 2 / g, with a diameter of 100~300nm.
[0015] A third aspect of the present invention provides the application of nanofiber-like molybdenum sulfide / carbon thermal battery composite cathode material in the preparation of thermal batteries.
[0016] The beneficial effects of this invention are: (1) In this invention, molybdenum salt is used as the molybdenum source and polymer compound is used as the carbon source. The nanofiber MoS2 / C thermal battery composite cathode material is prepared by combining high voltage electrospinning and high temperature sulfurization calcination. MoS2 is generated in situ during the carbon fiber formation process and contained in the nanofiber, which helps to improve the problems of uneven distribution of active materials, insufficient interface contact and discontinuous conductive network in traditional mechanical mixing methods.
[0017] (2) In the MoS2 / C composite cathode material prepared by this invention, the nanofibers form a continuous conductive network, which can improve the electron transport capability of the MoS2 active material, reduce the internal impedance and interfacial impedance of the electrode, thereby improving the ohmic polarization problem during the high-current discharge process of the thermal battery. This composite cathode material has a large specific surface area and an overlapping nanofiber pore structure, which can increase the contact area between the cathode material and the molten salt electrolyte, which is conducive to rapid ion transport and full utilization of active sites, thereby improving the discharge capacity and power output capability of the thermal battery.
[0018] (3) In this invention, the two-dimensional layered MoS2 is contained in carbon nanofibers. The carbon nanofibers can provide confined support and structural buffer for MoS2, reducing the volume change and structural stress accumulation of MoS2 during discharge, which is beneficial to improving the cycle stability and discharge safety of the cathode material. The composite cathode material has high thermal stability and can adapt to the instantaneous activation of the hot battery and the high-temperature discharge environment, reducing the thermal decomposition of active materials and reducing the risk of side reactions and thermal runaway caused by sulfur vapor.
[0019] (4) The preparation method of the present invention has a simple process, requires universal equipment, and has adjustable process parameters. It is suitable for continuous and large-scale preparation and has good prospects for engineering application. Attached Figure Description
[0020] Figure 1 : A process flow diagram of the preparation method of the nanofiber molybdenum sulfide / carbon thermal battery composite cathode material of the present invention; Figure 2 Nitrogen adsorption-desorption curves of the nanofiber molybdenum sulfide / carbon thermal battery composite cathode material obtained in Example 1; Figure 3 Thermogravimetric analysis curve of the nanofiber molybdenum sulfide / carbon thermal battery composite cathode material obtained in Example 1; Figure 4 : A physical image of the nanofiber-like molybdenum sulfide / carbon thermal battery composite cathode material obtained in Example 1; Figure 5 XRD pattern of the nanofiber molybdenum sulfide / carbon thermal battery composite cathode material obtained in Example 1; Figure 6 SEM image of the nanofiber molybdenum sulfide / carbon thermal battery composite cathode material obtained in Example 1, scale bar is 1 μm; Figure 7 SEM image of the nanofiber molybdenum sulfide / carbon thermal battery composite cathode material obtained in Example 1, scale bar is 200 nm; Figure 8 TEM image of the nanofiber-like molybdenum sulfide / carbon thermal battery composite cathode material obtained in Example 1; Figure 9 TEM image of the multilayer MoS2 distribution in the nanofiber molybdenum sulfide / carbon thermal battery composite cathode material obtained in Example 1; Figure 10 SEM image of the MoS2+C nanofiber material obtained in Comparative Example 2, scale bar is 50 nm; Figure 11 : Discharge performance diagram of the nanofiber molybdenum sulfide / carbon composite cathode material obtained in Example 1 used in a thermal battery; Figure 12: Discharge performance of the molybdenum disulfide / carbon nanofiber composite material obtained in Comparative Example 1 in a thermal battery; Figure 13 : Discharge performance of the MoS2+C nanofiber material obtained in Comparative Example 2 in a thermal battery; Figure 14 Example 1, Comparative Example 1 and Comparative Example 2: Comparison of the internal resistance variation curves of assembled batteries. Detailed Implementation
[0021] It should be noted that the following detailed descriptions are illustrative and intended to provide further explanation of this application. Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains.
[0022] As described in the background section, combining metal sulfides with carbon materials, such as combining MoS2 with carbon materials to prepare nanofibers, can improve the overall conductive network of the electrode and reduce the internal resistance of the battery to a certain extent. Nanoforming the active material can shorten the ion diffusion path and improve reaction kinetics. Existing electrospun MoS2 / carbon fiber materials mostly adopt precursor pre-vulcanization or simultaneous spinning vulcanization processes. Not only is the spinning solution prone to agglomeration and the fiber skeleton easily corroded and destroyed by the sulfur source, but the volatilization of downstream ionized sulfur at high temperatures is also serious, which is completely unsuitable for the high-temperature safety requirements of thermal batteries. Some disclosed post-vulcanization technologies are only applied to room temperature secondary batteries and have not been optimized for the conditions of instantaneous thermal shock, molten salt electrolyte, and ultra-high current discharge of thermal batteries.
[0023] Based on this, the present invention provides a nanofiber-like molybdenum sulfide / carbon thermal battery composite cathode material, its preparation method, and its application. First, molybdenum salt is prepared into a spinning solution and electrospun to ensure uniform distribution of the molybdenum salt within the nanofibers; then, the molybdenum salt is sulfided and the nanofibers are carbonized simultaneously through heat treatment. This invention employs an innovative process route of electrospinning film formation, vacuum curing, and post-fiber vulcanization, achieving multiple performance breakthroughs in the positive electrode: First, the fiber matrix is formed before vulcanization, preserving the three-dimensional network structure and enhancing the material's resistance to instantaneous thermal shock; the vulcanization reaction is controllable, precisely constructing a multi-layered MoS2 active structure, balancing high activity loading and volume buffering capacity; a pre-treatment deep impurity removal process reduces electrode internal resistance, effectively suppressing high-current polarization and improving discharge stability and capacity output; relying on reaction directionality and dual confinement, the volatilization of free sulfur is significantly reduced, helping to decrease the possibility of free sulfur volatilization and its side reactions with the negative electrode, thereby improving the safety of the thermal battery during high-temperature discharge and addressing high-temperature side reactions and thermal runaway issues; the self-supporting thin film structure eliminates the need for binders, optimizing electrode interface performance and energy density; simultaneously, the process is simple, the finished product has good consistency, and it balances performance in use and industrial value.
[0024] The MoS2 in the nanofiber-like molybdenum sulfide / carbon thermal battery composite cathode material obtained in this invention has a multilayer sheet structure. The tight composite of multilayer MoS2 nanosheets and the carbon fiber conductive network forms a continuous electron transport channel, reducing the contact impedance between the active and conductive phases, thereby improving charge transport capability under high current density discharge conditions. Single-layer MoS2 sheets are thin and have weak structural rigidity; the high-temperature shock during thermal battery activation easily causes sheet cracking and detachment. Multilayer MoS2, relying on layered stacking, forms stronger structural strength and thermal stability, with a thermal tolerance temperature exceeding 800℃, effectively buffering instantaneous thermal stress, inhibiting high-temperature decomposition of active materials, and fundamentally reducing the risk of thermal runaway. Single-layer structures are limited by morphology, resulting in low active material loading per unit volume, making it difficult to meet the high-capacity, high-power output requirements of thermal batteries. Multilayer MoS2 significantly increases the active component loading, and with a wide range of adjustable component design, it significantly improves battery discharge capacity and power density. Multilayer MoS2 exhibits superior intrinsic electron mobility compared to single-layer structures. Combined with the carbon fiber conductive network, it forms a synergistic system that significantly reduces electrode internal resistance and charge transfer impedance at high current densities, suppresses ohmic polarization, and ensures a stable discharge voltage plateau. Single-layer MoS2 lacks buffer space, and its discharge volume expansion easily leads to pulverization failure. The interlayer gaps in multilayer MoS2 act as natural buffer regions, working in conjunction with the carbon fiber skeleton to absorb structural stress, maintaining morphology integrity during long-term high-temperature discharge and significantly improving stability. The interlacing of multiple layers forms hierarchical channels, combined with a high specific surface area, increasing the contact area with the molten salt electrolyte and accelerating ion transport. Furthermore, the post-sulfurization process described in this application allows the multilayer structure to bind sulfur, reducing free sulfur volatilization and preventing side reactions between sulfur vapor and the negative electrode.
[0025] To enable those skilled in the art to better understand the technical solution of this application, the technical solution of this application will be described in detail below with reference to specific embodiments.
[0026] The test materials used in the embodiments of this invention are all conventional test materials in the art and can be purchased through commercial channels.
[0027] Example 1: Preparation of nanofiber-like MoS2 / C thermal battery composite cathode material like Figure 1 As shown, it includes the following steps: (1) Weigh 0.1g of polyacrylonitrile (PAN) powder and slowly add it to a beaker containing 1.9g of N,N-dimethylformamide (DMF) solution. Place the beaker on a magnetic stirrer and heat it to 50°C. Stir continuously at 400rpm until the powder is completely dissolved to obtain a colorless, transparent spinning base solution free of suspended impurities. Slowly add 0.9g of MoCl5 powder to the spinning base solution and stir continuously until the solution is homogeneous to obtain the spinning solution. Draw the above spinning solution into a 5ml syringe and load it into an electrospinning machine. Clamp the positive electrode to the tip of the syringe, set the spinning current to 0.5mA, the applied voltage to 25kV, the feed pump speed to 0.08rpm, the spinning temperature to 30°C, the humidity to 30%, and the distance between the spinning needle and the collecting device to 20cm. Use tin foil as a carrier to collect the nanofibers. Tin foil containing nanofibers was placed in a vacuum drying chamber at 160°C for 16 hours. Vacuum drying was used to remove residual solvents, improve the morphology retention of the fiber film, and prevent the nanostructure from collapsing during high-temperature processing, thus obtaining a cured fiber film.
[0028] (2) The cured fiber film was placed in a crucible and sublimed sulfur powder was added, wherein the mass ratio of fiber film to sulfur powder was 3:7. A tube furnace was set up to heat the film from room temperature to 700°C at a heating rate of 5°C / min in a nitrogen atmosphere of 25 sccm. The film was held at this temperature for 4 hours and then naturally cooled to room temperature to achieve carbonization and sulfidation, thereby obtaining the nanofiber MoS2 / C thermal battery composite cathode material. The MoS2 content in this embodiment was calculated to be 89.36 wt%.
[0029] Figure 2 The nitrogen adsorption-desorption curves for the nanofiber-like MoS2 / C thermal battery composite cathode material obtained in this embodiment are shown, with a specific surface area of 325 m². 2 / g.
[0030] Figure 3 The thermogravimetric analysis curves of the nanofiber MoS2 / C thermal battery composite cathode material obtained in this embodiment are shown. The thermogravimetric analysis results show that when the temperature is increased to 800℃ at 10℃ / min under a nitrogen atmosphere, the sample mass loss is less than 5%, and the composite cathode material has good thermal stability within 800℃.
[0031] Figure 4 This is a photograph of the nanofiber-like MoS2 / C thermal battery composite cathode material obtained in this embodiment.
[0032] Figure 5 The image shows the XRD pattern of the nanofiber-like MoS2 / C thermal battery composite cathode material obtained in this embodiment. Figure 5 It can be seen that the obtained composite cathode material contains characteristic peaks of MoS2 and amorphous carbon, but no other impurity peaks, indicating that the obtained composite cathode material is a composite of MoS2 and carbon materials.
[0033] Figure 6 , Figure 7 The image shows a SEM image of the nanofiber MoS2 / C thermal battery composite cathode material obtained in this embodiment. The carbon fibers of the obtained nanofiber MoS2 / C thermal battery composite cathode material have a diameter of about 200 nm and a uniform morphology.
[0034] Figure 8 , Figure 9 This is a TEM image of the nanofiber-like MoS2 / C thermal battery composite cathode material obtained in this embodiment. The obtained carbon fibers contain nano-two-dimensional layered MoS2.
[0035] In the composite material prepared in Example 1, multilayer two-dimensional MoS2 nanosheets are uniformly embedded in the carbon fiber matrix in an alternating stacked manner, without obvious agglomeration or segregation. The MoS2 layer structure is intact and tightly bonded to the carbon fiber skeleton; the multilayer MoS2 is completely covered and confined by the carbon fiber, and its distribution runs through the entire fiber, exhibiting excellent uniformity.
[0036] Example 2: Preparation of nanofiber-like MoS2 / C thermal battery composite cathode material (1) Weigh 1.0g of polyvinylidene fluoride and add it to a beaker containing 9.0g of N-methylpyrrolidone. Place the beaker on a magnetic stirrer and heat it to 60°C. Stir continuously at 400rpm until a colorless, transparent spinning base solution without suspended impurities is obtained. Slowly add 5.67g of MoCl5 powder to the spinning base solution and stir continuously until the solution is homogeneous to obtain the spinning solution. Draw the above spinning solution into a 5ml syringe and load it into an electrospinning machine. Clamp the positive electrode to the tip of the syringe, set the spinning current to 0.8mA, the applied voltage to 30kV, the feed pump speed to 0.10rpm, the spinning temperature to 35°C, the humidity to 40%, and the distance between the spinning needle and the collecting device to 30cm. Use tin foil as a carrier to collect nanofibers. Place the tin foil carrying nanofibers in a vacuum dryer at 160°C for 16h to solidify the fiber structure and prevent the nanostructure from collapsing during the high-temperature treatment to obtain a solidified fiber film.
[0037] (2) The cured fiber film was placed in a crucible and sublimed sulfur powder was added, wherein the mass ratio of fiber film to sulfur powder was 4:6. A tube furnace was set up to heat the film from room temperature to 650°C at a heating rate of 10°C / min in a nitrogen atmosphere of 30 sccm. The film was held at this temperature for 5 hours and then naturally cooled to room temperature to achieve carbonization and sulfidation, thus obtaining a nanofiber MoS2 / C thermal battery composite cathode material. The MoS2 content in this embodiment was calculated to be 89.86 wt%.
[0038] The specific surface area of the nanofiber-like MoS2 / C thermal battery composite cathode material obtained in this embodiment is 286 m².2 / g.
[0039] Comparative Example 1 The method described in Example 2 of the patent application CN 110289389A, which relates to a molybdenum disulfide / carbon nanofiber composite material and its preparation method, is as follows: Dissolve 7.5 g of ammonium molybdate tetrahydrate in 30 mL of deionized water to obtain an ammonium molybdate solution with a concentration of 0.25 g / mL. Ammonium molybdate solution was then added dropwise to 80 mL of 20 wt% ammonium sulfide solution. The mixture was stirred at room temperature for 10 min, resulting in the precipitation of red crystals. The precipitated red powder was obtained by filtration, which was the first product 2. The first product 2 was washed three times with anhydrous ethanol and tetrahydrofuran (THF), respectively. Finally, the precipitated red crystals were dried under nitrogen at room temperature for 48 h to obtain ammonium tetrathiomolybdate (AMT), which was the second product 2. 1 g of polyvinyl alcohol (PVA) was added to 10 mL of water and stirred at 60 °C for 2 h. Then, 1.5 g of the second product 2 (AMT) was added and stirred to form a homogeneous and stable red solution, which was the third product 2. The third product 2 was loaded into a 10 mL syringe connected to a metal needle and electrospun. The electrospinning process parameters were as follows: positive voltage 22 kV; negative voltage -2 kV; speed 0.075 mm / min; needle type 21 G; distance between the metal needle and the collecting metal plate 10 cm; internal temperature of the instrument 50 °C. The resulting nascent carbon nanofibers are designated as product 2. Product 2 is then vacuum-dried at 80°C for 24 hours, followed by heating to 600°C at a rate of 5°C / min under a nitrogen atmosphere and holding at that temperature for 1 hour. After cooling within the furnace, a molybdenum disulfide / carbon nanofiber composite material is obtained.
[0040] Comparative Example 2 The difference from step (1) of Example 1 is that MoCl5 powder is replaced with an equal amount of MoS2 powder. MoS2 nanofibers are then prepared.
[0041] The difference from step (2) of Example 1 is that no sulfur powder is added and heat treatment is performed to obtain MoS2+C nanofiber material.
[0042] Figure 10 To obtain the SEM image of the MoS2+C nanofiber material for Comparative Example 2, the obtained nanofiber-like MoS2 / C thermal battery composite showed that molybdenum sulfide was severely agglomerated on the carbon fiber surface.
[0043] Experimental Example: Performance Testing Eighty mg of each of the materials prepared in Example 1, Comparative Example 1, and Comparative Example 2 were used to press 12 mm positive electrode sheets into plates using a powder pressing process at a pressure of 10 MPa. A mixture of 50 wt% ternary lithium electrolyte (9.6 wt% LiF + 22 wt% LiCl + 68.4 wt% LiBr) and 50 wt% MgO was used as the separator material; 120 mg of this mixture was pressed into a 12 mm separator sheet at a pressure of 10 MPa. A lithium-boron alloy sheet with a diameter of 11 mm and a thickness of 1.2 mm (containing 60% lithium) was used as the negative electrode material. Single-cell batteries were assembled in an argon-filled glove box (with water and oxygen content both below 0.01 ppm), and these were designated as Example 1, Comparative Example 1, and Comparative Example 2, respectively. The solid molten salt inside the battery was activated to an ionic state using a heating activation method. The battery temperature was stabilized at 500°C during discharge, and the cutoff voltage was set to 0 V. The battery specific capacity was calculated based on the mass of the positive electrode material.
[0044] Discharge tests were conducted using a special thermal battery testing device (Bori Hengke: TBCH-550), with the discharge temperature set at 500℃, and at discharge rates of 50, 100, 200, 500, and 1000 mA / cm². 2 Discharge tests were conducted using the current density, and the battery polarization at the instant of current change was calculated according to Ohm's law, characterizing the trend of battery internal resistance change and average internal resistance. ΔV is the instantaneous voltage difference within 1 second before and after the current step; ΔI is the current difference corresponding to adjacent current density stages; the average internal resistance is the average of the internal resistance values calculated from the four current step calculations, and the results are shown in [reference needed]. Figures 11-14 .
[0045] like Figures 11-13 As shown, in Example 1, the initial voltage of the single-cell battery group was approximately 1.5V, and the MoS2 / C system exhibited superior electrochemical performance. In the graded current discharge test, the discharge rate successively reached 50, 100, 200, 500, and 1000 mA / cm². 2 At different current densities, the cumulative discharge specific capacity of the battery in Example 1 reached 20.7, 58.5, 134.2, 323.3, and 451.4 mAh / g, respectively, corresponding to discharge voltages of 1.48, 1.46, 0.95, 0.83, and 0V for each stage. This represents a 32.5% improvement in discharge capacity compared to the best-performing MoS2+C single-cell battery in the comparative examples. The initial discharge voltage of the single-cell battery in Comparative Example 1 was approximately 1.34V, and its discharge specific capacity at different current densities was lower than that of Example 1, with a discharge capacity of only 301.5 mAh / g at 0V. Comparative Example 2 used MoS2+C nanofiber material, with a discharge specific capacity of 340.8 mAh / g at a discharge cutoff voltage of 0V; its assembled battery performance was also lower than that of Example 1.
[0046] Depend on Figure 14 As can be seen, the internal resistance curve of Example 1 is located at the bottom, and the internal resistance of the battery during discharge is the smallest compared to Comparative Example 1 and Comparative Example 2. The average internal resistances of Example 1, Comparative Example 1, and Comparative Example 2 are 0.30, 0.34, and 0.33 Ω, respectively. The excellent electrochemical performance of the battery in Example 1 is attributed to the synergistic coupling effect between carbon nanofibers and layered molybdenum disulfide, which gives the MoS2 / C heterostructure good structural stability.
[0047] The above description is merely a preferred embodiment of this application and is not intended to limit this application. Various modifications and variations can be made to this application by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the protection scope of this application.
Claims
1. The application of a nanofiber-like molybdenum sulfide / carbon thermal battery composite cathode material in the preparation of thermal batteries, characterized in that, The applications are to improve the ohmic polarization problem during the high-current discharge process of thermal batteries, increase the discharge capacity and power output capability of thermal batteries, and improve the cycle stability and discharge safety of cathode materials. The nanofiber-like molybdenum sulfide / carbon thermal battery composite cathode material is prepared by the following method: (1) Polyacrylonitrile is added to N,N-dimethylformamide to form a spinning base solution. MoCl5 is added to the spinning base solution and mixed evenly. A molybdenum-containing nanofiber film is formed by high voltage electrospinning. The obtained nanofiber film is cured under vacuum conditions. The curing is carried out in vacuum drying at 160°C for 16 hours. (2) The cured nanofiber film and sulfur powder are placed in N2 for heat treatment to carbonize polyacrylonitrile and to in-situ sulfurize the molybdenum component from MoCl5 inside the carbon nanofibers to obtain nanofiber MoS2 / C thermal battery composite cathode material; the mass ratio of the nanofiber film to the sulfur powder is 3:7; the heating rate of the heat treatment is 5℃ / min, the temperature is 700℃, and the time is 4h; the flow rate of the N2 is 20-60sccm; the MoS2 is a multilayer MoS2 nanosheet, which is generated in-situ in an interleaved stacking form and embedded inside the carbon nanofibers.
2. The application according to claim 1, characterized in that, In step (1), the temperature at which the mixture is homogenized is 30~60℃.
3. The application according to claim 1, characterized in that, In step (1), the mass ratio of polyacrylonitrile to N,N-dimethylformamide is 5:95-15:85; the mass ratio of polyacrylonitrile to MoCl5 is 10:90-40:
60.
4. The application according to claim 1, characterized in that, In step (1), the parameters of the high-voltage electrospinning are: spinning current of 0.5-2mA, spinning voltage of 20-50kV, distance between spinning needle and collector of 15-40cm, spinning speed of 0.05-0.30rpm, spinning temperature of 20-50℃, and spinning humidity of 30-50%.
Citation Information
Patent Citations
Molybdenum disulfide / carbon nanofiber composite material and preparation method and application thereof
CN110289389A